2020
DOI: 10.1038/s41467-020-17923-w
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond X-ray emission study of the spin cross-over dynamics in haem proteins

Abstract: In haemoglobin the change from the low-spin (LS) hexacoordinated haem to the high spin (HS, S = 2) pentacoordinated domed deoxy-myoglobin (deoxyMb) form upon ligand detachment from the haem and the reverse process upon ligand binding are what ultimately drives the respiratory function. Here we probe them in the case of Myoglobin-NO (MbNO) using element-and spin-sensitive femtosecond Fe K α and K β X-ray emission spectroscopy at an X-ray free-electron laser (FEL). We find that the change from the LS (S = 1/2) M… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 53 publications
1
24
0
Order By: Relevance
“…The low repetition rate of the SACLA has an advantage in the use of a commercial optical parametric amplifier for the excitation light source so that the excited wavelength can be easily selected. The EH2 unit has a platform [42] designed for ultrafast liquid chemistry, which covers several complementary X-ray techniques, e.g., pump-probe XAFS [19,21,27,43,44], pump-probe X-ray emission spectroscopy (XES) [45], and pump-probe X-ray liquid scattering. The monochromatized X-ray pulses were focused with a Be compound refractive lenses (CRLs) [46] to give a beam size of 100 × 100 µm 2 at the sample position.…”
Section: Methodsmentioning
confidence: 99%
“…The low repetition rate of the SACLA has an advantage in the use of a commercial optical parametric amplifier for the excitation light source so that the excited wavelength can be easily selected. The EH2 unit has a platform [42] designed for ultrafast liquid chemistry, which covers several complementary X-ray techniques, e.g., pump-probe XAFS [19,21,27,43,44], pump-probe X-ray emission spectroscopy (XES) [45], and pump-probe X-ray liquid scattering. The monochromatized X-ray pulses were focused with a Be compound refractive lenses (CRLs) [46] to give a beam size of 100 × 100 µm 2 at the sample position.…”
Section: Methodsmentioning
confidence: 99%
“…The combination of high peak power and ultrashort duration of XFEL pulses enables efficient probing of dilute species of catalysts in solution with sufficient signal-to-noise ratio. Radiationsensitive molecular catalysts and metalloenzymes in solution are now routinely studied in XFELs to probe their steady states 14 and to capture intermediates that occur on slow 58,59 and ultrafast timescales [60][61][62] . However, at sufficiently high peak power, highly focused XFEL pulses start to create nonlinear effects that change the linear X-ray spectra [63][64][65][66][67] .…”
Section: Nature Reviews | Physicsmentioning
confidence: 99%
“…and can be performed off resonance with any incident photon energy above the absorption edge region of the absorbing metal (bOX 1), allowing the use of the full XFEL SASE pulse and combining the technique with scattering/diffraction. XFEL-based XES has been used widely to study changes in metal oxidation states and spin states of enzyme systems, including the haem Fe in cytochrome c 60,61 and in myoglobin 62 , the Mn 4 Ca cluster in photosystem II (PS II) 18,[57][58][59]73 , the dinuclear Mn-Fe site in ribonucleotide reductase (RNR) 18 (FigS 2a,3b) and the dinuclear Fe-Fe site in methane monooxygenase 74 . Numerous other photosensitive transition-metal complexes have been studied to understand the initial steps of photoexcitation and light-induced charge transfer, and the time-resolved XES provided detailed information about changes in the effective spin of the transition metal 70,71,75-80 (Fig.…”
Section: X-ray Emission Spectroscopy Xes Probes Occupied Statesmentioning
confidence: 99%
“…In the recent ultrafast XES study of NO photodissociation from myoglobin by Kinschel et al, they found spectroscopy evidence for both CT and intermediate spin states on the sub-picosecond timescale when the Fe-NO bond dissociates, supporting the conclusion that bond dissociation precedes the formation of the high spin 5 MC state. 112 The MLCT mechanism proposed for Fe-CO in hemoglobin and Fe-NO in myoglobin should not be operative for Fe(II)-S dissociation in cyt c because the Fe-S bond lacks p character. 113 Chergui et al, based on their ultrafast UV-visible pump-probe measurements, determined the electron in the p* orbital transfers to the metal d z 2 orbital to initiate Fe(II)-S dissociation.…”
Section: Mechanistic Studies Of Fe-s Bond Photo-dissociation In Cytochrome Cmentioning
confidence: 99%
“…In the recent ultrafast XES study of NO photodissociation from myoglobin by Kinschel et al , they found spectroscopy evidence for both CT and intermediate spin states on the sub-picosecond timescale when the Fe–NO bond dissociates, supporting the conclusion that bond dissociation precedes the formation of the high spin 5 MC state. 112 …”
Section: Applying Simultaneous Xes-xss To the Photo-physics And Photochemistry Of Iron Complexesmentioning
confidence: 99%